COMMUNICATION KARAOKE DEVICE PROVIDED WITH AUTOMATIC IMAGE COMPOSITING SYSTEM - UCHIDA MIZUKI; KITAMURA HIDEHITO (1999)
PROBLEM TO BE SOLVED: To provide a communication KARAOKE (orchestration without lyrics) device capable of displaying various images corresponding to many programs with comparatively few image data in connection with the progress of a musical program. SOLUTION: An image recording medium 18 consists of a 1st image recording part 18a for recording 1st image data such as subjects and a 2nd image recording part 18b for recording 2nd image data such as scenes, and the 1st and 2nd image data selected in accordance with each requested program and read out from the 1st and 2nd image recording parts 18a, 18b are composited to edit required image information by an image information edition circuit 19. Output information from the circuit 19 is composited with words telop data, and the composite data are reproduced and displayed.